I w ciemność idę, i już nie powrócę. O kognitywnej metaforze drogi w poezji Adama Asnyka - Różańska, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
This article attempts to answer the question, how is in the poetry of Adam Asnyk functioning the cognitive metaphor of way, how it is conceptualized, and also what are the relationships between conventionalized way of understanding the way element and the artistic text. It would be, therefore, important to restore richness of language and culture features of any given semanteme, that is to show it along with all collocations on the cultural background and to reconstruct the linguistic image of the world contained in general language. This article presents the semantics of the way semanteme, which in the poetry of Adam Asnyk exists in various forms.